Impact of Substitute Portland Cement with CKD on the Mechanical and Durability Characteristics of Cement Mortar. Issue 1 (March 2021) - Al-Faluji, Duaa; Al-Rubaye, Muna M.; Nasr, Mohammed Salah; Shubbar, Ali A.; Al-Khafaji, Zainab S.; Alkhayyat, Ahmed; Abdulraheem, Mustafa S.
Abstract: Cement mortar is a binding material that is made of cement, sand and water. In general, mixes of mortar are made of raw materials. However, using raw materials in producing mortar leads to many environmental and economic issues. One of the most common solutions to reduce these issues is replacing raw materials by waste and/or by-product materials; especially replacing cement. The aim of this research is to explore the characteristics of mortar mixes after partially replacing Ordinary Portland Cement (OPC) by Cement Kiln Dust (CKD) at three percentages (10%, 20% and 30%) in terms of initial and final setting time, compressive strength and Ultrasonic Pulse Velocity (UPV). The control mortar specimen (mortar containing OPC only) results were adopted for comparison with results of mortar mixes that incorporated CKD. Results showed that increment in CKD replacement percentages led to a decrement in the compressive strength and UPV and an increment in the setting time.